Numerical simulation study of tunneling process using TBM disc cutter under extremely hard rock condition - Huawei WANG; Zhengyang KANG; Yingcai WANG; Sijin LIU; Peng LIU (You-qi chuyun)
Objective The finite element method is recognized as a common tool in the realm of researching and developing new disc cutters tailored for hard rock applications. This study aims to construct coherent Finite Element Models (FEMs) to offer enhanced calculation accuracy and efficiency. Methods Drawing upon theoretical insights from rock fragmentation and materials science, a FEM linear cutting model was established to replicate the 19 inch smooth disc cutter used for tunneling across the Wuhu River, integrating the migmatitic granite stratum conditions prevalent in the Yangtze River Delta region. Notably, a grid refinement factor λ was introduced, and its values were maintained within the range from 0.5 to 4.0, through the local grid refinement technique. The subsequent computational results corresponding to different λ values were compared with the results of the Cutting Stress Model (CSM) modified by Rostami to verify the developed FEM. Results Although the value of λ exhibited no apparent influence on the rock-breaking behaviors shown by the FEM, it was found to be associated with both advance failure and excessive failure effects. This indicates that the accuracy and efficiency of the FEM are sensitive to the value of λ. Specifically, the accuracy of calculating the average rolling force and average vertical force initially decreased and then increased with rising values of λ. With λ=2.5, the average vertical forces from the FEM and the CSM got closest, with an approximation of 98.5%. With λ=3.0, the resulting average rolling forces of the two models were closest, with an approximation of 99.8%. In terms of efficiency, the time spent on calculations and solving increased with higher values of λ in the FEM. For instance, the time required at λ=4.0 was roughly 15 times that at λ=0.5. The computational results also suggested that a judicious selection of λ benefits both accuracy and efficiency. Conclusion The recommended value for λ stands at 3.0, serving as the optimal grid refinement factor for the FEM in simulation studies, presenting an enhancement in calculation efficiency of nearly 30%, compared with the results obtained at λ=2.5. The outcomes of this study lay down a theoretical framework for crafting FEMs with elevated calculation accuracy and efficiency for novel disc cutters tailored for hard rock applications.